Intelligent road and bridge monitoring system - ZHANG WEIJIAN; JI SANYOU (2014)
The utility model relates to an intelligent road and bridge monitoring system which comprises a vehicle detector, a first dynamic weighing device, a second dynamic weighing device, an LCD screen, a mechanical arm, an MCU processor and a bridge and road network monitoring center, wherein the allowed carrying capacities and dead weight data of different types of vehicles and dynamic weighting processing and mechanical arm controlling software are pre-stored in the MCU processor. The the vehicle detector, the mechanical arm, the first dynamic weighing device, the LCD screen and the second dynamic weighing device are connected with the MCU processor, and the MCU processor is connected with the bridge and road network monitoring center in a 3G wireless network mode. The intelligent road and bridge monitoring system can be mounted at a road or bridge to automatically detect vehicles passing by needless of on-site workers, overload vehicles are timely warned, and are recorded by the bridge and road network monitorin